Stable Dynamics Performance and High Efficiency of ABX3‐Type Super‐Alkali Perovskites First Obtained by Introducing H5O2 Cation - Zhou, Tingwei; Wang, Ming; Zang, Zhigang; Fang, Liang (Advanced energy materials, 2019)
Developing new ABX3‐type perovskites is very important for expanding the family of perovskites and obtaining excellent light absorbing material. One strategy is replacing A site atoms with super‐alkali atoms for the perovskites, but super‐alkali perovskites with stable dynamics performance and high efficiency have not been found until now. Herein, massive super‐alkalis, such as Li3O, Li2F, H5O2, and so on, are introduced into the cubic CH3NH3PbI3 perovskites, and the perovskites with these super‐alkalis are systematically studied by using ab initio molecular dynamics simulation and density functional theory based first principles calculations. Calculated results indicate that the perovskites with the super‐alkalis including metal atoms show unstable dynamics performance under normal temperature and pressure. On the contrary, the first obtainable super‐alkali perovskites of cubic H5O2MBr3 (M = Ge, Sn, Pb) and H5O2PbI3 show stable dynamics performance. They also show suitable tolerance factors, negative formation energies, tunable direct band gaps, and small effective hole and electron masses. Moreover, the calculated power conversion efficiencies of 23.17% and 22.83% are obtained for the single‐junction solar cells based on the cubic H5O2SnBr3 and H5O2PbBr3 perovskites, respectively. Introducing H5O2 cations into ABX3‐type perovskites, the cubic H5O2MBr3 (M = Ge, Sn, Pb) and H5O2PbI3 super‐alkali perovskites with suitable tolerance factors, negative formation energies, tunable direct band gaps, small carrier effective masses, stable dynamics performance and high efficiencies are obtained, which can be regarded as the excellent light absorbing materials of solar cells.